Characterisation of Churn Flow Coalescers (CFC) in vertical pipes - Kanu, Aimé Uzochukwu (2013)
The Gas-Liquid Cylindrical Cyclone (GLCC) separator is commonly used for the separation of oil and gas mixtures flowing from the well head. Similar to the design used by other separators, it has an inlet and two outlets for gas and liquid respectively. However, the inlet to the separator can either be single or dual type. The pipeline connection from the upstream preconditioning equipment (CFC) is inclined downwards and has a tangential inlet slot. The essence of having a downward inclination is to promote pre-separation of the fluid phases. On the other hand, a tangential inlet promotes circular fluid motion thereby inducing separation of the fluid phases by centrifugal forces.